2012
DOI: 10.1093/ndt/gfs129
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of hyperkalaemia-associated repolarization abnormalities in end-stage renal disease

Abstract: Background. Hyperkalaemia is a common potentially fatal complication of chronic kidney disease (CKD). It may manifest as electrocardiogram (ECG) changes, the earliest of which is T-wave 'tenting'. However, this occurs in less than half of episodes of hyperkalaemia. The aim of this study was to determine what other clinical features relate to the probability of T-wave tenting; and if there is a longer-term survival difference between patients who develop tenting and those who do not. Method. One hundred and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 47 publications
1
17
1
6
Order By: Relevance
“…Our study verified that age was an independent predictor of mortality and odds of death increased by 5% for each year increase in age. Contrary to other studies [9,12,13,15], our findings suggested that presence of chronic kidney disease or level of creatinine did not predict survival independently, this may reflect that other indicators of worsening kidney function such as eGFR are better predictors of outcome than serum creatinine alone [13]. It was also important to note that the presence of shock or use of inotropic agents was not associated with increased risk of mortality in patients with hyperkalemia.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study verified that age was an independent predictor of mortality and odds of death increased by 5% for each year increase in age. Contrary to other studies [9,12,13,15], our findings suggested that presence of chronic kidney disease or level of creatinine did not predict survival independently, this may reflect that other indicators of worsening kidney function such as eGFR are better predictors of outcome than serum creatinine alone [13]. It was also important to note that the presence of shock or use of inotropic agents was not associated with increased risk of mortality in patients with hyperkalemia.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the condition is associated with a variety of clinical presentations, EKG manifestations of hyperkalemia are generally progressive and proportional to the serum K+ and ventricular arrhythmias may be the first EKG finding of hyperkalemia. Sometimes, however, normal EKG may be seen even with very high serum potassium levels [1][2][3]9]. The management of hyperkalemia also depends on an understanding of the underlying physiology, cause of hyperkalemia and plasma potassium levels.…”
mentioning
confidence: 99%
“…Disease progression and increased hearth mortality are observed in chronic kidney disease under hypokalemia or hyperkalemia conditions and these effects are gender and race dependent [6]. Severe nephropathy with renal interstitial fibrosis and ventricular hypertrophy are seen in human patients under hyperkalemia states [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…En la hiperpotasemia la onda T es típicamente elevada (>10 mm ó 1 mV), angosta, simétrica y en punta (picuda o aspecto de tienda de campaña), suele aparecer precozmente con niveles de Sin alteraciones Con alteraciones leve moderada severa 61% 39% 50% 50% 50% 50% potasio 5,5 mEq/L, sobre todo en las derivaciones precordiales izquierdas (21). Sin embargo, existe una predisposición individual para que este cambio en la onda T se manifieste en el ECG.…”
Section: Discussionunclassified